Respuesta :
Expanding the product is simple enough:
[tex](x-11)(x+13)=x^2+2x-143[/tex]
Then
[tex]\displaystyle\int(x-11)(x+13)\,\mathrm dx=\dfrac{x^3}3+x^2-143x+C[/tex]
We could also use a subsitution like [tex]u=x-11[/tex], so that [tex]u+24=x+13[/tex] and [tex]\mathrm du=\mathrm dx[/tex]:
[tex]\displaystyle\int u(u+24)\,\mathrm du=\int(u^2+24u)\,\mathrm du=\dfrac{u^3}3+12u^2+C[/tex]
[tex]\implies\displaystye\int(x-11)(x+13)\,\mathrm dx=\dfrac{(x-11)^3}3+12(x-11)^2+C[/tex]
(which is differs from the first result by a constant, so it's still valid)
Answer:
1/3x^3+x^2-143x+c
Step-by-step explanation:
i got it right on the test